2021
DOI: 10.1002/joc.7139
|View full text |Cite
|
Sign up to set email alerts
|

Winter AOD trend changes over the Eastern Mediterranean and Middle East region

Abstract: The present study documents the winter aerosol optical depth (AOD) trends over the Eastern Mediterranean and Middle East (EMME) region using MERRA‐2 and moderate‐resolution imaging spectroradiometer (MODIS) collection 6.1 data. A significant upward AOD trend was identified during the years 2000–2010, whereas the AOD followed a significant downward trend during the years 2010–2017. Our analysis indicates that aeolian dust is the main contributor to AOD changes. The winter AOD changes are related to meteorologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…Likewise, the long‐term dust variability over the past 10–15 years across the Eastern Mediterranean indicated a decrease (−4% per year) in dust AOD (Marinou et al., 2017). These results are in accord with those of other studies (De Meij et al., 2012; Hsu et al., 2012; Pozzer et al., 2015; Shaheen et al., 2021; Yoon et al., 2014) based on data from satellite sensors. Other regional studies reported increasing trends in dust frequency over Israel in 1958–2006 (Ganor et al., 2010) and 2001–2015 (Krasnov et al., 2016), while in Cyprus, a statistically significant decreasing tendency in the frequency of dust events (−7 events per year) was detected during 2006–2017 (Achilleos et al., 2020).…”
Section: Historical Greenhouse Gas Emissions and Pollutionsupporting
confidence: 93%
See 1 more Smart Citation
“…Likewise, the long‐term dust variability over the past 10–15 years across the Eastern Mediterranean indicated a decrease (−4% per year) in dust AOD (Marinou et al., 2017). These results are in accord with those of other studies (De Meij et al., 2012; Hsu et al., 2012; Pozzer et al., 2015; Shaheen et al., 2021; Yoon et al., 2014) based on data from satellite sensors. Other regional studies reported increasing trends in dust frequency over Israel in 1958–2006 (Ganor et al., 2010) and 2001–2015 (Krasnov et al., 2016), while in Cyprus, a statistically significant decreasing tendency in the frequency of dust events (−7 events per year) was detected during 2006–2017 (Achilleos et al., 2020).…”
Section: Historical Greenhouse Gas Emissions and Pollutionsupporting
confidence: 93%
“…Several active deserts are located in the region such as the Egyptian and Nubian deserts in the northeastern Sahara; the Rub‐Al Khali, An Nafud and Al Dahna deserts in the Arabian Peninsula; the Negev desert in Israel; the Syrian‐Iraqi desert; the alluvial flood plains in Mesopotamia; the Dasht‐e Kavir and Dasht‐e Lut deserts in Iran as well as the desiccated, ephemeral or dried‐up lakes like Urmia, Jazmurian and Hamouns in Iran (Cao et al., 2015; Francis, Alshamsi, et al., 2019; Francis, Chaboureau, et al., 2021; Francis, Eayrs, et al., 2019; Ginoux et al., 2012; Kaskaoutis et al., 2016). The regional dust activity is highly sensitive to weather conditions (Bodenheimer et al., 2018; Hermida et al., 2018; Nabavi et al., 2016; Shaheen et al., 2021) and climate perturbations (Hemming et al., 2010; Hoerling et al., 2012). Dust storms originating in the Middle East strongly affect the regional atmospheric radiation budget, cyclogenesis, monsoon circulation and air quality (Francis et al., 2020; Q. Jin et al., 2016; Soleimani et al., 2020; Solmon et al., 2015).…”
Section: Historical Greenhouse Gas Emissions and Pollutionmentioning
confidence: 99%
“…Furthermore, spatial distribution and time series of several atmospheric parameters, such as AOD 550 , dust loading, dust surface concentration, and dry and wet dust deposition, were taken over the study region from the Modern-Era Retrospective analysis for Research and Applications (MERRA-2) re-analysis database, 5.12.4 model, at a horizontal resolution of 0.5 • × 0.625 • (latitude, longitude) [104,105]. MERRA-2 has been proved as an accurate database for monitoring of dust aerosols, spatial variability, and trends over the Middle East, exhibiting considerable agreement with MODIS observations [35,86]. Moreover, ERA-5 reanalysis [106], with a 31-km horizontal resolution and 137 levels spanning from the surface of the Earth to 0.01 hPa, was used to obtain meteorological fields of surface vector winds at 0.75 • × 0.75 • spatial resolution.…”
Section: Data Set and Methodologymentioning
confidence: 94%
“…Temporal evolution, intra-seasonal to inter-annual variation, and long-term trends in SDS have a great importance in the desert/arid regions and in affected areas, such as the East Mediterranean-Middle East (EMME) region [35,[84][85][86]. In this study, statistical analysis of dust events is performed at the five most polluted cities in SW Iran covering a period of 22 years (from 1997 to 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The RH affects desert humidification and has a vital influence on the summer AOD distributions over the AP (Shaheen et al ., 2021). The spatial distribution of RH at 850 hPa exhibits the maximum RH over the southeastern AP, Yemen, and Ethiopia and the minimum RH (<10%) over the central AP, Arabian Gulf, northern Red Sea, and Egypt (Figure 3c).…”
Section: Model Validation and Prevailing Atmospheric Conditionsmentioning
confidence: 99%